Metabolic changes of the blood metabolome after a date fruit challenge. (October 2018) - Mathew, Sweety; Halama, Anna; Abdul Kader, Sara; Choe, Minkyung; Mohney, Robert P.; Malek, Joel A.; Suhre, Karsten
Graphical abstract: Highlights: Khlas and Deglet Nour fruit consumption lead to different plasma metabolic profiles. Products of metabolism of cinnamate and ferulate increase after date consumption. Plasma metabolic levels correspond to differences between Khlas and Deglet Nour. Phytochemicals remain bio-available after date fruit consumption. Abstract: Date fruits are rich in phytochemicals that have anti-oxidative properties and are therefore considered as functional foods. However, it is unclear which part of the date metabolites actually enter the blood stream and remain bioavailable to exert any beneficial action. To answer this question, we conducted a nutritional challenge study in which we monitored plasma metabolome of 21 healthy volunteers after intake of Khlas, Deglet Nour, and glucose at five time points. Among the 1089 identified blood circulating metabolites, we found molecules that were specific to date consumption, including metabolites of the polyphenols ferulic-, caffeic-, and vanillic acid. Consumption of the sucrose-rich Deglet Nour led to a substantial increase in blood sucrose levels. Interestingly, consumption of serotonin-rich dates did not alter serotonin blood levels, but resulted in a sharp increase in its breakdown product 5-hydroxyindolacetate. We elucidated metabolites present in the blood after date consumption with potential health beneficial effect.